Keraliya Cikitsa Paddhati - A Complete Guide to Specialized Keralan Ayurveda Treatment Procedures Based on Dharakalpah-A Book Review - Lunavat, Riddhi Bharat; Binitha, A; Jigeesh, P P (International Research Journal of Ayurveda & Yoga, 2023)
Background: Various Socio-political and geographical reasons helped Kerala to provide a favorable atmosphere to flourish Ayurveda in this land. Inestimable contributions made by Ayurvedic practitioners in Kerala led to developments in terms of procedures as well as medicine. Knowledge about the subtler nuances of performing various therapeutic procedures, along with their clinical implications was recorded by eminent practitioners in Kerala. However, it was dispersed amongst various regional texts, and it needed to be lined under one heading. Authors Pavana Jayaram and Manoj Sankaranarayana managed to gather all these pieces of information together and presented them in the form of this book named - Keraliya Cikitsa Paddhati. Methodology: The presented book was studied, analyzed, and compared with other contemporary works on a similar subject. Body and Analysis: The present book is written in Sanskrit and English. It contains 304 pages, and its price is 500 INR. This book was published by Sarada Mahadeva Iyer, Ayurvedic Educational and Charitable Trust, Tamil Nadu. The book was published in 2010. It comprises three sections. The first section encompasses the Sanskrit text Dharakalpa which sheds light on the Procedure named Dhara – one of the specialized Keraliya treatment modalities. Following it, the book presents the first and only english commentary on Dharakalpa written by the authors – Pavana and Manoj. The second section of the book comprises an extensive review of the available literature about external treatment modalities (Bahih-parimarjana cikitsa). The third section of the book encompasses various necessary preparations required before commencing the procedure. It caters both, epistemological knowledge and pragmatic usage of external treatment modalities for the Ayurvedic fraternity. ‘Keraliya Cikitsa Paddhati’ is the first and only attempt made in such a direction where the traditional knowledge is not merely translated but very well explored through available literature.